2019
DOI: 10.2169/internalmedicine.1218-18
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Paraganglioma

Abstract: A 57-year-old woman was admitted with lower abdominal pain and bloody bowel discharge. She was diagnosed with rectal tumor by colonoscopy, and a biopsy was performed. Surgery was performed, resulting in a diagnosis of rectal paraganglioma. Since recurrence was confirmed three years later, reoperation was done, and chemotherapy with cyclophosphamide, vincristine and dacarbazine (CVD) was subsequently carried out for further recurrence. After the administration of up to 15 courses of CVD, we delivered best suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The immunohistochemical results were similar to those in our case; all cases were positive for neuroendocrine markers, and S-100 highlighted sustentacular cells. Furthermore, there are currently three reports of paraganglioma originating in the rectum, and we concluded that the microscopic morphological features and immunohistochemical results were similar to our case, with main organ-like nests (3,5,8). However, the cell proliferation activity in these three rectum-origin cases was high, and the index of Ki-67 was 20%, 41%, and 50%, respectively (3, 5, 8) Among the eight cases mentioned above, only three performed SDHB immunohistochemical staining and were diagnosed with SDHx-related paragangliomas.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The immunohistochemical results were similar to those in our case; all cases were positive for neuroendocrine markers, and S-100 highlighted sustentacular cells. Furthermore, there are currently three reports of paraganglioma originating in the rectum, and we concluded that the microscopic morphological features and immunohistochemical results were similar to our case, with main organ-like nests (3,5,8). However, the cell proliferation activity in these three rectum-origin cases was high, and the index of Ki-67 was 20%, 41%, and 50%, respectively (3, 5, 8) Among the eight cases mentioned above, only three performed SDHB immunohistochemical staining and were diagnosed with SDHx-related paragangliomas.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of PPGL is approximately 0.6 cases per 100,000 people ( 2 ). The peak incidence of PPGL is observed in 20–40-year-old individuals, the average age of onset of hereditary cases is 24.9 years, the average age of onset of sporadic cases is 43.9 years, and there are no differences among the incidences in terms of sex ( 3 ). In the 2017 WHO classification of endocrine tumors, PPGLs were classified as malignant tumors from previous benign, borderline, or biologically uncertain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, she suffered the recurrent tumor metastases and died of multiple metastases of paraganglioma 6 years after the initial operation. Patient 2 was previously reported with clinicopathological data and chemotherapy in detail by Araki et al [3], however, SDHBimmunohistochemistry was first carried out this time. In the present paper, we added data of SDHBimmunohistochemistry and compared pathologic findings of Case 1 and Case 2.…”
Section: Case Reportmentioning
confidence: 99%
“…Case 2 had metastasis at the time of the initial operation, received no adjunctive therapy after surgery and was well at the 9-month Endocrine Journal Advance Publication follow-up [2]. Case 3 had lymph node metastasis three years after the operation, suffered multiple metastases in different organs during her life, and expired approximately 5 years after the operation [3]. The common characteristic of our cases, Case 4 and Case 5 was the lack of SDHB-positive immunohistochemistry (SDHBdeficiency).…”
Section: Colorectal Paragangliomasmentioning
confidence: 99%
See 1 more Smart Citation